STUDI SEDIMEN PADA ANAK SUNGAI SAKA KANAN DI DAS TENGGARONG KABUPATEN KUTAI KARTANEGARA - Mulyadi, Rachmad (Indonesia University of Education, 2008)
Tenggarong watershed has several Sub-watershed. One of them Saka Kanan river basin that be one of the present environment quality depreciation. Drainage basin knowable as good or bad conditon based on erosion level in surface soil and sedimentation level in river. This research aims to detect rate of flow water level, sedimet load pregnancy flies and load basis for will detect environment quality standard. Saka Kanan watershed as one of the Sub-watershed that will give sedimet and load base material towards Tengarong Watershed. Method survey field with watch closely and measures rate of river flow, take river water sample to at sedimet load analysis flies. As sedimentation determination and water quality analysis. Terba Station in has criteria resim water as big as 1,45 % that criteria very ugly while station bensamar as big as 6,95 % also in category very ugly. Sediment load measurement result flies in Terban station sedimet load between 28.60-685 mg/l enter in good category up to very ugly. Station bensamar has value between 37.50-725.75 mg/l enter in good category up to very ugly.Â Keywords : River Flow Level, Sedimet load, Saka Kanan Watershed